Hydraulic fracturing in ice boreholes: Theory and tests - Chen, Chen; Zhang, Han; Liu, Shuyuan; Jin, Chengcai; Chen, Yong; Zhang, Nan; Talalay, Pavel (Polar Science, 2019)
Hydraulic fracturing is the well-known phenomenon that can occur intentionally, as it is used in the petroleum industry to stimulate the flow of natural gas or oil, or naturally, for example, as a reason for calving of ice shelves. For many years, occurrence of hydro-fracturing in ice boreholes was much disputed as there was no clear evidence that it exists. This paper proposes a method of estimating the over-pressure caused by hydraulic fracturing in ice allowing to identify a critical balance between hydraulic fracture pressure and overburden ice pressure at the certain depth of ice borehole. A series of experiments to study hydraulic fracturing behaviour using a set of artificial ice samples and a triaxial fracturing testing system were performed. The tests results were in good agreement with theory with the variation of just 0.9–8.7%. Results from the fracture experiments confirm that in real ice borehole, hydraulic fracturing phenomenon is possible if the horizontal differential stress is large within a fissured ice borehole wall. For fracture morphology, vertical fractures formed and extended nearly perpendicular to the minimum horizontal principal stress direction. The proposed estimation method allows drillers to adjust drilling fluid density for reasons of safety and environmental security. journal article